Two novel plasmids harbouring the multiresistance gene cfr in porcine Staphylococcus equorum - Ning Xie; Tengfei Ma; Yuan Gao; Jiani Fu; Chune Tan; Zheng Wang; Zhuo Wang; Henrike Krüger-Haker; Andrea T. Feßler; Congming Wu; Jianzhong Shen; Stefan Schwarz; et al. (Journal of Global Antimicrobial Resistance)
Background: The emergence and transmission of the multidrug resistance gene cfr have raised public health concerns worldwide. Objectives: Multidrug-resistant Staphylococcus equorum isolates can pose a threat to public health. In this study, we have characterised the whole-genome of one Staphylococcus equorum isolate harbouring two distinct cfr-carrying plasmids. Methods: Antimicrobial susceptibility testing was performed by broth microdilution. Genomic DNA was sequenced using both the Illumina HiSeq X Ten and Nanopore MinION platforms. De novo hybrid assembly was performed by Unicycler. Genomic data were assessed by in silico prediction and bioinformatic tools. Results: Staphylococcus equorum isolate SN42 exhibited resistance or high MICs to linezolid, erythromycin, tetracycline, oxacillin, clindamycin, virginiamycin, tiamulin, chloramphenicol and florfenicol. It carried two cfr-harbouring plasmids: the RepA N-family plasmid pSN42–51 K and the Inc18-family plasmid pSN42–50 K. These two plasmids exhibited low structural similarities to the so far reported cfr-carrying plasmids. Both plasmids harboured an arsenic resistance operon, copper and cadmium resistance genes as well as the lincosamide-pleuromutilin-streptogramin A resistance gene lsa(B). In addition, plasmid pSN42–51 K carried two erm(B) genes for macrolide-lincosamide-streptogramin B resistance, the streptomycin resistance gene ant(6)-Ia as well as mercury resistance genes while pSN42–50 K was associated with the heavy metal translocating P-type ATPase gene hmtp. The co-carriage and co-existence of these antimicrobial resistance and heavy metal resistance genes increases the likelihood of co-selection of the cfr-carrying plasmids. Conclusion: This is the first report of S. equorum carrying two distinct cfr-carrying plasmids, underscoring the need for ongoing surveillance to address the potential dissemination of multi-drug resistance in bacteria from food-producing animals to ensure food safety and public health.